Floristic Studies in Bulbostylis Kunth (Cyperaceae) - Shaikh , Rafeeque Ishakhoddin (Plantae Scientia, 2021)
Present study is on our own critical observations on fresh plant material collected from the different parts. The observations are also based on herbarium specimens. Relevant data from literature have been referred for comparative study and conclusion including recent nomenclature. The study of Bulbostylis Kunth provides a detailed taxonomic description, illustration and relevant information for its easy identification in the field. Three species are collected and are described. The present report is hoped to provide basic material for further research in Cyperaceae.